Pancreas transplantation with grafts obtained from donation after cardiac death or donation after brain death results in comparable outcomes - Bleszynski, Michael S.; Parmentier, Catherine; Torres-Hernandez, Alejandro; Ray, Samrat; Yousuf, Anila; Norgate, Andrea; Schiff, Jeffrey; Shwaartz, Chaya; Sapisochin, Gonzalo; McGilvray, Ian; Selzner, Markus; Reichman, Trevor W. (Frontiers in Transplantation, 2023)
Pancreas organ shortages and long recipient waitlist times are critical components that limit recipients from receiving a pancreas transplant. Over the last decade, our center has been using donation after cardiac death (DCD) donors as an adjunct to donation after brain death (DBD) donors to expand the organ pool. The aim of this study was to compare recipient and graft survival between DCD and DBD recipients. A retrospective single center propensity matched analysis (2011-2020) of 32 DCD vs 96 DBD pancreas transplants was performed. 8-year recipient survival was similar between DCD and DBD groups (87.4% vs 92.7%, p=0.35) as was simultaneous kidney and pancreas transplant (SPK) 8-year kidney (88.9 vs 96.9%, p=0.219) and pancreas graft survival (77.4% vs 86.7%, p=0.344). There was no difference in vascular thrombosis rate between DCD and DBD pancreas grafts (3.1% vs 7.3%, p=0.73). DCD kidneys had a higher rate of DGF vs DBD kidneys (28.1% vs 6.3%, p=0.004), without any significant difference in long term kidney failure (12.5% vs 8.3%, p=0.5). Recipients of DCD grafts demonstrate equivalent long-term patient and graft survival compared to DBD recipients for pancreas transplantation. Increased utilization of well selected DCD donors is a safe strategy to increase the donor pool